Molecular characterization and evaluation of pectinase and cellulase production of Penicillium spp. - Pereira, Jorge Fernando; Queiroz, Marisa Vieira de; Gomes, Eliane Aparecida; Muro-Abad, Júpiter Israel; Araújo, Elza Fernandes de (Biotechnology Letters, 2002)
Penicillium species were analyzed with molecular markers and for pectinase and cellulase production. RAPD and PCR-RFLP analysis indicated high polymorphism among at least 5 of 10 Penicillium species. Five species were chosen for pectinase and cellulase production in liquid medium and four of which appeared similar based on molecular analyses. P. brevicompactum and P. griseoroseum gave the highest pectinase production and were highly divergent by molecular techniques.
Keywords: Cellulase; Pectin lyase; Penicillium; Polygalacturonase; RAPD; rDNA